Review Artikel: Pengaruh Jenis Eksipien terhadap Disolusi Tablet - Najma Kamila Zahra; Intan Nova Kaesa; Elina Jatindria; Stella Reflya Pramudita; Dzikrina Adibah Salma (Journal of Educational Innovation and Public Health, 2026)
This study aimed to analyze the effect of excipient variations on tablet dissolution profiles and the underlying mechanisms. The research method used was a literature review by examining scientific articles published between 2021 and 2026. Literature sources were obtained from Google Scholar, ResearchGate, and relevant national and international journals. The analysis was conducted descriptively and comparatively on the use of excipients such as binders, disintegrants, lubricants, and surfactants in tablet formulations and their effects on dissolution parameters. The review results showed that the type of excipient significantly affects the dissolution profile of tablets. Binders can improve the mechanical strength of tablets but may slow down dissolution, while disintegrants accelerate tablet disintegration and increase the dissolution rate. Lubricants such as magnesium stearate may inhibit liquid penetration due to their hydrophobic properties, whereas surfactants can enhance drug solubility and accelerate the dissolution process. In addition, the concentration and combination of excipients also influence porosity, tablet hardness, wettability, and drug release mechanisms. Therefore, the selection and optimization of excipients are crucial in developing tablet formulations with optimal dissolution profiles and therapeutic effectiveness.